2016
DOI: 10.3389/fphys.2016.00641
|View full text |Cite
|
Sign up to set email alerts
|

Strength and Aerobic Physical Exercises Are Able to Increase Survival of Toxoplasma gondii-Infected C57BL/6 Mice by Interfering in the IFN-γ Expression

Abstract: Physical exercise has been implicated in several immunophysiological improvements, particularly during the aging process, when an immunocompromised status could be established. Toxoplasma gondii is a protozoan parasite that causes a widespread opportunistic infection, which may present severe consequences, mainly to the fetus and immunocompromised patients. It is estimated that one-third of the human population worldwide has been infected by this parasite, being the reactivation during immunesenescence an unex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…Physical exercise has been identified as a protective factor for health and well-being by increasing the immunological response [2], due to its anti-inflammatory activity [3,4]. Physical exercise of moderate intensity [5] induces a discharge of catecholamines (adrenaline and norepinephrine), leading to an increase in the concentration of T lymphocytes in the vascular compartment [6].…”
Section: Introductionmentioning
confidence: 99%
“…Physical exercise has been identified as a protective factor for health and well-being by increasing the immunological response [2], due to its anti-inflammatory activity [3,4]. Physical exercise of moderate intensity [5] induces a discharge of catecholamines (adrenaline and norepinephrine), leading to an increase in the concentration of T lymphocytes in the vascular compartment [6].…”
Section: Introductionmentioning
confidence: 99%
“…Advances in the research on molecular and physiological responses to exercise have given prominence to the field of exercise immunology. In this sense, it is known that physical activity contributes significantly to stimulating crucial components of the immune system [20,21], promoting the host's defense against parasites [22][23][24], treating cancer [25], and regulating autoimmune and hypersensitivity components [26][27][28]. It has also been reported that physical exercise is essential for vaccine effectiveness [29][30][31][32], which is crucial for the new COVID-19 vaccines.…”
Section: Introductionmentioning
confidence: 99%